(untitled) (Heritage, 2024)
It is a very challenging problem to analyze the performance of the economy of each country based on multi-criteria decision-making methods. Based on that, this paper analyzes the performance of the Serbian economy based on the DIBR-TOPSIS method. According to the results of the TOPSIS method, the best performance of the Serbian economy was in 2016. The following are: 2021, 2012, 2018, 2019, 2010, 2011, 2013, 2017, 2015, 2020 and 2014. Overall, taking the period 2018-2021, performance improved of the Serbian economy, with the exception of 2020. The poor performance of the Serbian economy in 2020 was partly influenced by the Covid-19 pandemic. The performance of the Serbian economy was affected by real GDP growth, consumer prices, foreign exchange reserves, export of goods and services, import of goods and service, unemployment, earnings, consolidated financial result, public debt, exchange rate and GDP. With the increase of liquidity, solvency, degree of open economy, as well as with mitigation of exposure to financial risk, the improvement of the performance of the Serbian economy can be significantly influenced. In addition, it should be emphasized that recently the performance of the Serbian economy has been affected to a certain extent by the global political climate, the Covid-19 pandemic and the energy crisis. The digitization of the entire operation of companies from all economic sectors plays a significant role in this. Effective control of these and other factors can significantly influence the achievement of the target performance of the Serbian economy.